2018
DOI: 10.1002/ejic.201800451
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Complexes with Cross‐Bridged Cyclams: Synthesis and Use in Alcohol and Water Oxidation Catalysis

Abstract: A class of iron(III) complexes containing diversely substituted cross-bridged cyclams (1-R,R′: 1-Me,Me, 1-Me,Et, 1-Et,Et, 1-Me,Bn, 1-Bn,Bn) has been prepared and characterized.(1-R,R′) complexes catalyze the oxidation of alcohols to ketones in green conditions, by using tert-butylhydroperoxide as the oxidant in aqueous solutions. They also exhibit catalytic [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Based on molecule 12,t he development of macrocyclic ligand based WOCs hasb ecomea na ttractive topic ( Figure 7). Af amilyo fs tructural analogues (27)(28)(29)(30)(31)o fc omplex 8,w ith variouse lectron-donating or -withdrawing substituents in the ortho and para positions of the pyridine ligand, were synthesized by Costas et al in 2013t oe valuate the electronic effects on single-site iron catalysts for water oxidation. [27] With modification on the ortho position of the pyridine moiety,c omplex 30 showeda ctivity with aT ON of only 25 AE 3a nd aT OF of 80 AE 1h À1 ;t hese values are much lower than those of the mother complex 12,a nd complex 31 displayed no activityf or water oxidation.…”
Section: Is Water Oxidation Catalysis With Nonheme Iron Complexes Undmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on molecule 12,t he development of macrocyclic ligand based WOCs hasb ecomea na ttractive topic ( Figure 7). Af amilyo fs tructural analogues (27)(28)(29)(30)(31)o fc omplex 8,w ith variouse lectron-donating or -withdrawing substituents in the ortho and para positions of the pyridine ligand, were synthesized by Costas et al in 2013t oe valuate the electronic effects on single-site iron catalysts for water oxidation. [27] With modification on the ortho position of the pyridine moiety,c omplex 30 showeda ctivity with aT ON of only 25 AE 3a nd aT OF of 80 AE 1h À1 ;t hese values are much lower than those of the mother complex 12,a nd complex 31 displayed no activityf or water oxidation.…”
Section: Is Water Oxidation Catalysis With Nonheme Iron Complexes Undmentioning
confidence: 99%
“…[30] Ruffo et al also reported ac lass of iron complexes (35-39)c ontaining crossbridged cyclam ligandsw ith diverse substituents for NaIO 4driven water oxidation. [31] Thep resence of at least one methyl substituent is necessary to have reasonable activity:w ith two methyl groups (35)t he highest TOF is observed, while one methyl ando ne ethyl (36)p roduce the highest TON. In the last case, the best compromiseb etween accessibility to the metal centera nd its steric protection is obtained.…”
Section: Is Water Oxidation Catalysis With Nonheme Iron Complexes Undmentioning
confidence: 99%
See 2 more Smart Citations
“…We now have focused our attention on diiron compounds. Iron offers access to a wider range of oxidation states, and Fe‐PDI and ‐cyclam complexes are uniquely suited for a variety of redox and organometallic reactions, including several of the aforementioned biologically relevant reactions . We envisioned that the combined scope of reactions facilitated by the two types of Fe compounds might give rise to unique activities.…”
Section: Introductionmentioning
confidence: 99%